2001
DOI: 10.1890/0012-9658(2001)082[1433:pfantr]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Protein Fingerprinting: A New Technique Reveals Extensive Conspecific Brood Parasitism

Abstract: Conspecific brood parasitism occurs in many birds and some insects, fishes, and amphibians. Here, we develop and test a novel molecular technique for ecological analysis, protein fingerprinting (PF), based on isoelectric focusing electrophoresis (IEF) in immobilized pH gradients. It is applied here to albumen from birds' eggs and permits accurate identification of eggs laid by different females. This technique greatly clarifies female alternative reproductive tactics and laying patterns in brood‐parasitic Comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(32 citation statements)
references
References 48 publications
1
31
0
Order By: Relevance
“…Nevertheless, despite this limitation, non‐invasive sampling is suitable for estimating individual reproductive success. The combination of non‐invasive sampling and other methods, such as protein fingerprinting (Andersson and Åhlund 2001) and estimation of CBP based on egg morphology (Pöysä et al 2009), might in part overcome these drawbacks.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, despite this limitation, non‐invasive sampling is suitable for estimating individual reproductive success. The combination of non‐invasive sampling and other methods, such as protein fingerprinting (Andersson and Åhlund 2001) and estimation of CBP based on egg morphology (Pöysä et al 2009), might in part overcome these drawbacks.…”
Section: Discussionmentioning
confidence: 99%
“…Conspecific brood parasitism can be the result of joint laying by related females in a kin‐structured population of females formed as the result of limited dispersal, like among ducks. When the parasite is a relative, the cost to the host is mitigated by inclusive fitness gains from being related to offspring hatched from parasite eggs (Andersson and Åhlund 2000, 2001). Thus, the parasitism will produce related offspring, and hence select for within‐brood cooperation.…”
Section: Conspecific Brood Parasitismmentioning
confidence: 99%
“…We also collected egg albumen from 126 eggs from 20 nests found during laying or early incubation (1–3 days). To collect albumen, we punctured a small hole through the egg shell, removed approximately 200–300 μL of egg albumen with a syringe (Andersson & Åhlund 2001), and then sealed the hole with Aron Alpha Instant Krazy Glue ® (ethyl cyanoacrylate). Albumen samples were immediately stored on ice, and placed at −20 °C until protein fingerprint analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Egg albumen is of maternal origin, and exclusively represents the genotype of the female that laid the egg rather than that of the developing embryo. Andersson & Åhlund (2001) demonstrated that protein bands are both reproducible and genetically polymorphic across females, providing resolution sufficient to detect parasitic eggs and sometimes the females who laid them.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation